On Structural Optimization of the Propeller Blade - Aleshin, Mikhail; Smirnov, Aleksandr; Murzina, Margarita; Boldyrev, Yuri (International Journal of Engineering and Technology, 2018)
The results of the structural optimization of propeller blades are presented taking into account its composite structure and pitch change mechanism of the propeller and using FSI (Fluid-Structure Interaction) approaches.  The optimality criterion of the problem is the propeller thrust with optimization parameters being the characteristics of the internal structure of the propeller blade made from a composite. Together with the optimization of the blade shape, the problem is considered which concerns the reduction of the deformations caused by loads occurring during the operation of the propeller, since significant deformations of the blades lead to decreased thrust.Thus, the following optimization problem can be formulated: to find the optimal configuration of the composite material and its micro-geometrical parameters along the height of the blade to minimize deformations and increase the thrust of the propeller.  At the same time, the optimization parameters are limited by the weight of the propeller and the strength characteristics.The technique presented in the paper allows us to obtain the reliable values of thrust and reduce the estimated computational time.  The influence of the structure of the composite material on the mechanical properties of the blades is shown; the values of deformation of the blades under the action of centrifugal and aerodynamic loads are given.